Akibat Hukum Nikah Siri Terhadap Hak Anak Dan Isteri Ditinjau Dari Kompilasi Hukum Islam - Dinda Ediningsih Dwi Utami; Taufik Yahya (Universitas Jambi, Fakultas Hukum, 2022)
The aims of this study are to: 1) find out and analyze how the responsibility of parents towards children from unregistered marriages is seen from the Compilation of Islamic Law; 2) find out and analyze the legal consequences of the rights of children and wives from unregistered marriage in terms of the Compilation of Islamic Law. Research methods. This type of research is normative juridical. The research approach, namely, the Legislative Approach (Statute approach) and the Conceptual Approach (Conceptual Approach). Research result. 1) Parental Responsibilities Towards Children of Siri Marriage in Review From the Compilation of Islamic Law. a) Responsibility for the birth certificate, because it is a certificate resulting from the civil registration of a person's birth. b) Responsibility for Inheritance Rights. Children born from unregistered marriages or in civil law are called children out of wedlock, because their mothers cannot prove their marriage certificates. 2) The legal consequences of the rights of children and wives from unregistered marriages are reviewed from the Compilation of Islamic Law. As a result of the child being unable to obtain a birth certificate, it can be seen from the request for a birth certificate submitted to the civil registry office. Meanwhile, due to the law of unregistered marriage for the wife, the wife is not considered a legal wife. ABSTRAK Tujuan penelitian ini adalah untuk: 1) mengetahui dan menganalisis bagaimanakah tanggung jawab orang tua terhadap anak dari nikah siri di ditinjau dari Kompilasi Hukum Islam; 2) mengetahui dan menganalisis bagaimanakah akibat hukum terhadap hak anak dan isteri dari nikah siri ditinjau dari Kompilasi Hukum Islam. Metode Penelitian. Tipe penelitian dalam ini adalah yuridis normatif. Pendekatan penelitian, yaitu, Pendekatan Perundang-undangan (Statute approach) dan Pendekatan Konseptual (Conseptual Approach). Hasil penelitian. 1) Tanggung Jawab Orang Tua Terhadap Anak dari Nikah siri di Tinjau Dari Kompilasi Hukum Islam. a) Tanggung jawab terhadap akta kelahiran, karena adalah akta hasil pencatatan sipil dari hasil peristiwa kelahiran seseorang. b) Tanggung Jawab Terhadap Hak Warisan. Anak yang lahir dari hasil nikah siri atau dalam hukum perdata disebut dengan anak diluar nikah, karena ibunya tidak dapat membuktikan akta pernikahannya. 2) Akibat hukum terhadap hak anak dan isteri dari nikah siri ditinjau dari Kompilasi Hukum Islam. Akibat terhadap anak adalah anak tidak dapat mengurus akta kelahiran, hal itu bisa dilihat dari permohonan akta kelahiran yang diajukan kepada kantor catatan sipil. Sedangkan akibat hukum perkawinan siri bagi isteri, Isteri tidak dianggap sebagai isteri sah.